Re-Envisioning Peacekeeping : The United Nations and the Mobilization of Ideology - Debrix, Franois (Book collections on Project MUSE., 1999)
Time and again the United Nations has deployed peacekeeping missions in trouble spots around the globe: Iraq, Somalia, Bosnia, Rwanda. Has peace ensued? Have these missions, in fact, made any difference in the disorder and destruction they are purported to forestall? Or are they, as Franois Debrix contends in this critical revisiting of UN interventions, an illusionmore virtual peacekeeping than actual interventions in international affairs?